2012
DOI: 10.1007/s12630-012-9825-2
|View full text |Cite
|
Sign up to set email alerts
|

Complications of single-injection ultrasound-guided infraclavicular block: a cohort study

Abstract: Introduction In recent studies on ultrasound-guided infraclavicular block (ICB), the authors have favoured a single injection posterior to the axillary artery rather than multiple injections; however, procedural complications and success rates associated with single-injection ultrasound-guided ICB are not well known. We undertook an observational study to evaluate the success rates of experienced and non-experienced operators performing ICBs and to identify the complications associated with ultrasound-guided s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…There are only a limited number of large studies of ultrasound‐guided ICB, and in common with smaller studies, none of these reported the occurrence of pneumothorax . In studies with ≥ 500 blocks plus our own observational study, the risk of pneumothorax is 0.04% (95% CI 0.0–0.101) out of 4736 nerve blocks performed.…”
Section: Discussionmentioning
confidence: 78%
“…There are only a limited number of large studies of ultrasound‐guided ICB, and in common with smaller studies, none of these reported the occurrence of pneumothorax . In studies with ≥ 500 blocks plus our own observational study, the risk of pneumothorax is 0.04% (95% CI 0.0–0.101) out of 4736 nerve blocks performed.…”
Section: Discussionmentioning
confidence: 78%
“…Higher than expected incidence was reported by the Dartmouth registry of 12,668 US-guided blocks (persistent at 6 months; 0.9/1000; 95% CI, 0.5-1.7) 50 and a case series of 627 US-guided infraclavicular blocks (short-term follow-up not specified; 8/1000; 95% CI, 0-20). 45 Conversely, the Hospital for Special Surgery registry of 1169 US-guided interscalene and supraclavicular blocks reported an incidence that was lower than expected (resolved by 3 months; 0/1000; 95% CI, 0-0.3). 46 Case reports of long-term and permanent nerve injury in the setting of US guidance have since emerged.…”
Section: Table 3 Strength Of Evidence-the Effect Of Us Guidance On Pmentioning
confidence: 87%
“…In addition to supraclavicular block data, no pneumothorax was identified during an observational study of 627 US-guided infraclavicular blocks. 45 Although the predicted incidence has decreased during the past 5 years, pneumothorax has been reported despite US guidance using the interscalene, 85 supraclavicular, 63,86 and infraclavicular 87 approaches. Although it seems that the incidence of pneumothorax associated with UGRA is substantially less than with the classic supraclavicular approaches, it is unclear if the incidence is less than that experienced during the 1980s and 1990s using landmark-based techniques that were developed to direct needle trajectory away from the lung.…”
Section: Hemidiaphragmatic Paresismentioning
confidence: 99%
“…Interestingly, there was no apparent difference in the incidence of complications between experienced and non-experienced operators. 45 The infraclavicular block was described as safe and effective when no intraoperative or immediate postoperative complications were noted by Keschner and colleagues 46 in 248 block procedures. Similar to the interscalene and supraclavicular approaches, reduced or paradoxical ipsilateral hemidiaphragmatic movement was observed (26%) and Horner's syndrome was seen in 12% of 35 patients.…”
Section: Infraclavicular Approachmentioning
confidence: 99%